PERAN STRATEGIS ADMINISTRASI SEKOLAH DALAM MENINGKATKAN PERKEMBANGAN FISIK MOTORIK ANAK USIA DINI - Supratna, Hana; Deni, Asep; Fuadah, Tsani Tsamrotul (Pascasarjana Universitas Pendidikan Ganesha, 2025)
The golden period in human development is important because environmental stimulation and effective educational management are key factors in achieving optimal growth. The main issues discussed in this study are the effectiveness of administration in managing educational programs, the effectiveness of Human Resources (HR), and difficulties in policy implementation. This study aims to analyse school administration strategies that can improve the physical and motor development of children enrolled in TPA Idrisiyyah Daycare. This research methodology uses a qualitative approach, with data collection techniques through interviews with school representatives and teachers, as well as curriculum analysis. Based on the research findings, the school administration has an important role in ensuring that the curriculum is play-based, optimising student learning, and improving the standards of educator human resources. The primary focus of this study is on the relationship between the curriculum and children's needs, as well as the limited number of qualified caregivers. The research findings indicate that innovative and well-structured administration can create a learning environment that supports children's holistic development through teacher training recommendations and collaboration with other learners.